Truth beyond the ‘trigger puller’: moral accountability, transitional (in)justice and the limitations of legal truth - Hearty, Kevin (International journal of transitional justice, 2021)
This article critically examines how existing truth recovery processes have, and how proposed truth recovery processes might, address the issue of shoot-to-kill in Northern Ireland. In contrast to ongoing legacy case prosecutions of British Army veterans, it argues that truth recovery processes should adopt a maximalist conceptualization of truth and responsibility. This, it is argued, necessitates differentiating between legal truth and structural truth, and between legal, political and moral responsibility. It is further submitted that such an approach would reflect the importance of identifying and understanding patterns (looking at similar cases collectively) and context (looking at the socio-political-legal backdrop to them) when establishing the ‘broad circumstances’ around disputed killings. This approach would allow truth recovery to advance beyond low-level ‘trigger pullers’ to ensure ‘moral accountability’ for the complicity of other actors within the state apparatus.